The 'K-Beauty': An opportunity to benefit from Free Trade Agreement between Colombia and South Korea? (2020)
"K-Beauty" (Korean Beauty) can be considered as an explicit representation of the South Korean cosmetic sector and a phenomenon that has begun to influence the global cosmetic industry itself. Similarly, this phenomenon has influenced trends and consumption habits in the field of skin care. This article analyzes the characteristics of the South Korean cosmetic sector with the aim of making an academic contribution to the study of one of the most dynamic and innovative industries in the world. Making this characterization is of particular importance as natural and active ingredients obtained from Colombian biodiversity can be potentially used in Korean skincare formulations. Which represents an opportunity for Colombian companies in the Korean cosmetic-industry value chain. This is the result of a comprehensive literature review of the Korean cosmetic industry. The review has been complemented with semi-structured interviews conducted in South Korea during 2017 and 2018 with the support of consumers and scholars from Kyung Hee University (Seoul) and representatives of the Korean cosmetic industry. This is the product of the current research carried out by the Observatory for the Negotiation and Implementation of Trade Agreements (ONAAC after its initials in Spanish) of Universidad EAFIT (International Studies Group) on the opportunities for the agribusiness and biotechnology sector derived from the FTA between Colombia and South Korea